Nanofiber composites for biomedical applications - Ramalingam, Murugan; Ramakrishna, Seeram (Woodhead Publishing series in biomaterials, 2017)
Nanofiber Composite Materials for Biomedical Applications presents new developments and recent advances in nanofiber-reinforced composite materials and their use in biomedical applications, including biomaterial developments, drug delivery, tissue engineering, and regenerative medicine. Unlike more conventional titles on composite materials, this book covers the most innovative new developments in nanofiber-based composites, including polymers, ceramics, and metals, with particular emphasis on their preparation and characterization methodology. Selected case studies illustrate new developments in clinical and preclinical use, making the information critical for the development of new medical materials and systems for use in human health care, and for the exploration of new design spaces based on these nanofibers. This book is essential reading for those working in biomedical science and engineering, materials science, nanoscience, biomedical nanotechnology, and biotechnology.--Provided by publisher.